Intranodal Palisaded Myofibroblastoma: A Case Report (Pulse, 2022)
Intranodal palisaded myofibroblastoma is a rare benign soft tissue tumor almost always arising from inguinal lymphnodes. It usually present as a painless, slow growing inguinal mass. We report herein a case of an intranodal palisaded myofibroblastoma occurring in a 43-year-old man along with its salient clinicopathologic features and differential diagnosis.Pulse volumel.11 January-December 2018-2019 p.19-21